Modelling Stochastic Fibrous Materials with Mathematicaʼ - Sampson, William Wyatt. (Engineering Materials and Processes,, 2009)
Recent developments in the use of electrospun fibrous materials, for application as scaffolds for tissue engineering and in the application of carbon fibrous materials in fuel cells, has generated new interest in the dependence of the properties and structure of these materials on those of their constituent fibres. Modelling Stochastic Fibrous Materials with Mathematicaʼ provides an overview of the structure of stochastic fibrous materials, and the use of Mathematicaʼ to develop models describing their structure and performance. Modelling Stochastic Fibrous Materials with Mathematicaʼ provides an introduction to the techniques of statistical geometry and probabilistic modelling for non-mathematicians, and assumes no previous experience of Mathematicaʼ. Using accessible notation and by providing examples of Mathematicaʼ code, expressions are derived for the structural characteristics of stochastic fibrous materials, providing insights into the ways these depend upon each other and the extent to which they can be modified in the laboratory or in a manufacturing environment. Modelling Stochastic Fibrous Materials with Mathematicaʼ is a valuable resource for researchers and engineers in the paper and non-wovens industries and for those applying non-woven fibrous architectures in composites, fuel cells and filtration applications. The text is highly relevant also to researchers developing applications for electrospinning technologies. A trial version of Mathematicaʼ 6.0 can be downloaded from http://www.wolfram.com/books/resources, by entering the licence number L3250-9882. Mathematicaʼ notebook files containing the code presented in each chapter can be downloaded from http://www.springer.com/978-1-84800-990-5.